2018
DOI: 10.1016/j.bja.2018.05.075
|View full text |Cite
|
Sign up to set email alerts
|

Advance-care-planning and end-of-life discussions in the perioperative period: a review of healthcare professionals' knowledge, attitudes, and training

Abstract: Whilst the risk of dying after an operation in the UK is very small, the volume of surgery means that there are 20 000e25 000 deaths each year. For these patients and others who suffer major complications, critical illness often leads to a loss of capacity. If wishes are not discussed in advance, the patients may be excluded from meaningful involvement in decisions affecting their care. The preoperative period has been postulated as one where advance care planning could begin by engaging in voluntary conversat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…8 Likewise, a review of ACP and end-of-life discussions in the perioperative period found that, although providers seemed to view these discussions positively, limited educational and training content was available. 9 Despite the limited evidence to this point regarding perioperative ACP, there are a few populations where this approach has been studied. In 2018, Kata et al 10 studied the addition of ACP discussions to the preoperative process for elderly patients and found that it increased the number of designated surrogates, AD, and documents scanned into the medical record.…”
Section: Discussionmentioning
confidence: 99%
“…8 Likewise, a review of ACP and end-of-life discussions in the perioperative period found that, although providers seemed to view these discussions positively, limited educational and training content was available. 9 Despite the limited evidence to this point regarding perioperative ACP, there are a few populations where this approach has been studied. In 2018, Kata et al 10 studied the addition of ACP discussions to the preoperative process for elderly patients and found that it increased the number of designated surrogates, AD, and documents scanned into the medical record.…”
Section: Discussionmentioning
confidence: 99%
“…There is also an opportunity to educate future dentists about their impact by participating in an important, albeit difficult journey with their patients who are terminally ill or facing life-threatening disease or procedures. 20,21 Training for oral healthcare professionals to educate patients about their ACP options and guidance in navigating this process is sparse. This is not only an important element of dental education, but also an essential element of training for any healthcare professional involved in high-risk interventions.…”
Section: Discussionmentioning
confidence: 99%
“…There is also an opportunity to educate future dentists about their impact by participating in an important, albeit difficult journey with their patients who are terminally ill or facing life‐threatening disease or procedures . Training for oral healthcare professionals to educate patients about their ACP options and guidance in navigating this process is sparse.…”
Section: Discussionmentioning
confidence: 99%
“…The literature supports this assertion as ACP is not routinely included in the perioperative period leading to high-risk surgery. 8 The impact of the variation in attitude towards ACP between specialties requires further exploration. From the foundation doctors' perspective (theme A), the complexity of decision making within surgical and some interventional specialties was a barrier to holding ACP discussions due to limited experience.…”
Section: Education and Developing Clinical Practicementioning
confidence: 99%